PARTISIFASI PETANI DALAM KEGIATAN PENYULUHAN USAHATANI PADI SAWAH SISTEM TANAM JAJAR LEGOWO DI KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA; I DEWA GEDE SUARTA (GANEC SWARA, 2020)
Lowland rice farming with jajar legowo’s planting system causes an increase in production which is originally 6 tons / hectare to 8.8 tons / hectare, but until now not all farmers have adopted the technology. This research is conducted in West Lombok Regency with survey techniques, with descriptive data analysis. The results show that: the participation of farmers in the extension activities of paddy farming with jowo legowo’s planting system is quite high in number with level of participation is 161.25 Some of the obstacles faced by farmers in extension activities are as follows: collide with other activities, there is boredom in participating in counseling because they think it wastes time, the delivery of material is not in accordance with the planting patterns planned by farmers and the benefits are still lacking. There are still many farmers who do not adopt the technology, with the reason that: planting with a row planting system requires more time, requires more seeds, requires more fertilizer and more work conditions, ultimately impacting the costs incurred by the farmers. To increase farmers' participation in extension activities, more intensive training is needed by field extension workers (PPL), so that they can change the behavior of farmers and want to adopt the technology